Electrophotographic conductive member, process cartridge, and electrophotographic image forming apparatus

By designing a conductive layer with a specific structure in the conductive components of electrophotography, the problem of fogging caused by uneven developer transfer under low charging bias voltage was solved, achieving high-quality image formation and improving the performance of image forming equipment.

CN119717432APending Publication Date: 2025-03-28CANON KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411351596.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-06
Filing Date
2024-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In electrophotographic image forming equipment, reducing the charging bias voltage causes the developer to transfer to the non-exposed areas of the photosensitive component, resulting in fogging and affecting image quality.

Method used

An electrophotographic conductive component is employed, comprising a conductive layer consisting of a cross-linked product matrix containing a first rubber and multiple domains dispersed in the matrix. The domains include cross-linked products of a second rubber and conductive particles, and satisfy a specific volume resistivity relationship and impedance range to ensure suppression of reverse fogging under low charging bias voltage.

Benefits of technology

It effectively prevents fogging in electrophotographic images under low charging bias voltage, ensuring high-quality image formation and improving the stability and image quality of the image forming equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119717432A_ABST
    Figure CN119717432A_ABST
Patent Text Reader

Abstract

The invention relates to an electrophotographic conductive member, a process cartridge, and an electrophotographic image forming apparatus. An electrophotographic conductive member includes: a conductive layer disposed on an outer surface of a support, in which the conductive layer includes a plurality of domains dispersed in a matrix, the plurality of domains containing a crosslinked product of a second rubber and conductive particles, an outer surface of the electrophotographic conductive member is composed of a substrate and an exposed portion of a domain exposed on the outer surface of the electrophotographic conductive member, an impedance of the electrophotographic conductive member is 1.0 * 10 < 3 > to 1.0 * 10 < 8 > Omega, and when the specific region is a first region and a second region, the specific region is a second region. A volume resistivity R1 of a portion that is not the conductive particles in the first region and a volume resistivity R2 of a portion that is not the conductive particles in the second region satisfy R1 > R2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrophotographic conductive member, a process cartridge, and an electrophotographic image forming apparatus. Background Art

[0002] The electrophotographic image forming apparatus includes a charging member, a transfer member, and a developing member. The charging member is a member that generates discharge between the charging member and the electrophotographic photosensitive member to charge the surface of the electrophotographic photosensitive member. The developing member is a member that controls the charge of the developer coated on its surface by friction charging, provides a uniform charge amount distribution, and uniformly transfers the developer to the surface of the electrophotographic photosensitive member according to the applied electric field. The transfer member is a member that transfers the developer from the electrophotographic photosensitive member to a printing medium such as paper or an intermediate transfer member, while generating discharge to stabilize the transferred developer.

[0003] In the electrophotographic image forming process, the surface of the photosensitive member is charged, and then the charged surface of the photosensitive member is exposed to draw a latent image, and a developer is transferred to the latent image on the surface of the photosensitive member by a developing member and transferred to a paper medium by a transfer member.

[0004] In recent years, in response to the demand for energy saving of electrophotographic image forming apparatuses, it is considered to reduce the voltage applied to a conductive member such as a charging member, a developing member, or a transfer member.

[0005] For example, by reducing the voltage applied between the charging member and the photosensitive member as the charged member (hereinafter, also referred to as "charging bias"), the voltage applied to the developing member or the transfer member is also reduced, and energy saving can be achieved in the electrophotographic image forming apparatus.

[0006] Japanese Patent Application Publication No. 2020-166209 discloses a charging member capable of suppressing the occurrence of fogging of electrophotographic images. In the above charging member, the conductive layer has a matrix-domain structure in which domains containing a crosslinked product of a second rubber and conductive particles are dispersed in a matrix containing a crosslinked product of a first rubber. Summary of the invention

[0007] The present inventors have attempted to set the charging bias applied between the charging member and the electrophotographic photosensitive member to a voltage lower than the general charging bias (e.g., -1,300 V) when forming an electrophotographic image using the charging member according to Japanese Patent Application Publication No. 2020-166209 (e.g., -700 V to -900 V, more specifically, -800 V). As a result, in the case where the charging bias is reduced, the developer is also transferred to the non-exposed portion of the photosensitive member surface to which the developer is not initially transferred, and as a result, so-called "fogging" may occur on the electrophotographic image.

[0008] According to at least one aspect of the present disclosure, the charging bias can be set to, for example, -700 V to -900 V. The present disclosure is intended to provide an electrophotographic conductive member that can prevent fogging on an electrophotographic image even when a low charging bias as described above is used. In addition, at least one aspect of the present disclosure is intended to provide a processing box that facilitates high-quality electrophotographic image formation. In addition, at least one aspect of the present disclosure is intended to provide an electrophotographic image forming device capable of forming high-quality electrophotographic images.

[0009] At least one aspect of the present disclosure provides an electrophotographic conductive member including:

[0010] a support having an electrically conductive outer surface; and

[0011] A conductive layer is provided on the outer surface of the support, wherein

[0012] The conductive layer includes a matrix including a cross-linked product of a first rubber and a plurality of domains dispersed in the matrix,

[0013] the plurality of domains include a cross-linked product of a second rubber and conductive particles,

[0014] at least a portion of the plurality of domains is exposed on an outer surface of the electrophotographic conductive member,

[0015] The outer surface of the electrophotographic conductive member is composed of the matrix and the exposed portion of the domain exposed on the outer surface of the electrophotographic conductive member,

[0016] When the electrode is directly provided on the outer surface of the electrophotographic conductive member and an AC voltage with an amplitude of 1 V and a frequency of 1.0 Hz is applied between the outer surface of the support and the electrode under an environment with a temperature of 23° C. and a relative humidity of 50%, the impedance is 1.0×10 3 to 1.0×10 8 Ω, and

[0017] When the domain exposed on the outer surface of the electrophotographic conductive member is the domain A, and in the cross section of the domain A in the thickness direction of the conductive layer, the maximum length of the domain A in the thickness direction of the conductive layer is Ld,

[0018] The region with a thickness of 0.1×Ld on the side farthest from the support in the cross section of the domain A is the first region, and

[0019] When the region with a thickness of 0.1×Ld on the side closest to the support in the cross section of the domain A is the second region,

[0020] The volume resistivity R1 of the portion that is not the conductive particles in the first region and the volume resistivity R2 of the portion that is not the conductive particles in the second region satisfy R1>R2.

[0021] At least one aspect of the present disclosure provides a process cartridge configured to be detachably mounted to a main body of an electrophotographic image forming apparatus, the process cartridge including the electrophotographic conductive member of the present disclosure.

[0022] At least one aspect of the present disclosure provides an electrophotographic image forming apparatus including the electrophotographic conductive member of the present disclosure.

[0023] According to at least one aspect of the present disclosure, an electrophotographic conductive member that helps prevent fogging on an electrophotographic image when a charging bias is low can be obtained. In addition, according to at least one aspect of the present disclosure, a process cartridge that can stably form a high-quality electrophotographic image can be obtained. In addition, according to at least one aspect of the present disclosure, an electrophotographic image forming apparatus that can stably form a high-quality electrophotographic image can be obtained. Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a schematic cross-sectional view of a conductive roller according to one aspect of the present disclosure;

[0025] Figure 2 is a schematic cross-sectional view of a process cartridge;

[0026] Figure 3 is a schematic diagram of an electrophotographic image forming apparatus;

[0027] Figure 4A and Figure 4B is an illustration of impedance measurement;

[0028] Figure 5 is an enlarged cross-sectional view of the vicinity of the surface of the conductive layer of the conductive roller according to one aspect of the present disclosure; and

[0029] Figure 6 is an illustrative diagram of a domain at least partially exposed on an outer surface of a conductive layer of a conductive roller according to an aspect of the present disclosure. DETAILED DESCRIPTION

[0030] In the present disclosure, the descriptions of “from XX to YY”, “XX to YY (XX~YY)” each indicating a numerical range means a numerical range including the lower limit and the upper limit as endpoints, unless otherwise specifically stated. When the numerical range is stated step by step, the upper limit and the lower limit of each numerical range may be optionally combined. In addition, in the present disclosure, descriptions such as “at least one selected from the group consisting of XX, YY and ZZ” and the like mean any one of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, and a combination of XX, YY and ZZ.

[0031] The present inventors have studied the cause of fogging on an electrophotographic image when the charging member according to Japanese Patent Application Laid-Open No. 2020-166209 has a low charging bias.

[0032] First, the mechanism of occurrence of fogging will be described. Here, the potential of the surface of the photosensitive member or the magnitude (height) of the potential such as a charging bias refers to the magnitude (height) in the case of comparing absolute values.

[0033] In the process of forming an electrophotographic image, a charging bias is applied to the charging member to charge the surface of the photosensitive member, and then the charged surface of the photosensitive member is exposed to draw an electrostatic latent image. Next, a voltage (development bias) is applied to the developing member that carries the developer. Then, the developer charged to the normal polarity (negative) is transferred to the electrostatic latent image on the surface of the photosensitive member by the potential difference between the electrostatic latent image portion on the surface of the photosensitive member and the surface of the developing member. At this time, the potential difference between the surface of the photosensitive member of the non-exposed portion and the surface of the developing member is called Vback. The value of Vback is highly correlated with the value of fogging. When Vback is small, the electric field used to keep the developer on the developing member becomes weak, and fogging (ground fogging) tends to increase. On the other hand, when Vback is large, the developer with the opposite polarity (positive) is transferred to the surface of the photosensitive member, and fogging (reverse fogging) tends to increase. The developer with the opposite polarity transferred to the surface of the photosensitive member due to the reverse fogging is less likely to be transferred to the surface of the printing medium or the intermediate transfer member having a lower potential than the surface of the photosensitive member of the exposure portion. Therefore, although the influence on the image is small, the consumption of the developer may increase.

[0034] During the research, the inventors paid attention to the conductive domains exposed on the outer surface of the charging member according to Japanese Patent Application Publication No. 2020-166209. In the charging member according to Japanese Patent Application Publication No. 2020-166209, it is believed that electrons are sequentially transferred between multiple domains from the conductive support of the elastic layer to the outer surface of the elastic layer to generate electronic conductivity, and finally discharge is generated from the domain exposed on the surface of the charging member toward the electrophotographic photosensitive member. Although there is a non-conductive matrix between the domains inside the elastic layer, since the domain with low volume resistivity is exposed, it is easy to cause slight discharge unevenness on the outer surface of the elastic layer. As a result, it is presumed that slight potential unevenness occurs on the surface of the photosensitive member. When the charging bias is low, the surface potential difference between the exposed part and the non-exposed part of the photosensitive member becomes small, and as a result, the setting width of the development bias is also narrowed. Therefore, there is a tendency to reduce the development bias and increase Vback in order to preferentially reduce background fogging that may cause image defects. It is presumed that, as described above, as a result of increasing Vback, even when there is slight surface potential unevenness of the photosensitive member, the reversal fogging increases.

[0035] Therefore, the present inventors have found that in order to suppress the reverse fogging when a low charging bias is applied, it is necessary to control the volume resistivity of the portion other than the conductive particles in the thickness direction of the conductive layer in the domain exposed on the outer surface of the conductive member. As a result of further studies based on this finding, it was found that when an electrophotographic conductive member (hereinafter, also simply referred to as a conductive member) satisfying the following requirements (A) and (B) is used as a charging member, the reverse fogging can be suppressed even when a low charging bias is applied.

[0036] Requirement (A)

[0037] When the electrode is directly provided on the outer surface of the conductive member and an AC voltage with an amplitude of 1 V and a frequency of 1.0 Hz is applied between the outer surface of the support and the electrode under an environment with a temperature of 23°C and a relative humidity of 50%, the impedance is 1.0×10 3 to 1.0×10 8 Ω.

[0038] Requirement (B)

[0039] When the domain exposed on the outer surface of the electronic photographic conductive member is domain A, and in the cross-section of domain A in the thickness direction of the conductive layer, the maximum length of domain A in the thickness direction of the conductive layer is Ld, the area with a thickness of 0.1×Ld on the side farthest from the support body in the cross-section of domain A is the first region, and the area with a thickness of 0.1×Ld on the side closest to the support body in the cross-section of domain A is the second region, the volume resistivity R1 of the portion that is not conductive particles in the first region and the volume resistivity R2 of the portion that is not conductive particles in the second region satisfy R1>R2.

[0040] In the following, each requirement will be described in detail.

[0041] Requirement (A)

[0042] Requirement (A) indicates the degree of conductivity of the conductive layer. A conductive member showing such an impedance value can suppress an excessive increase in the amount of discharge current when used as a charging member. As a result, it is possible to prevent the occurrence of potential unevenness in charging due to abnormal discharge. It is possible to suppress the occurrence of insufficient charging due to insufficient total amount of discharged charge.

[0043] According to the requirement (A), the impedance is preferably 1.3×10 3 to 9.2×10 7 Ω, more preferably 5.0×10 3 Up to 5.0×10 7 Ω, and more preferably 1.0×10 4 to 1.0×10 7 Ω.

[0044] The impedance according to requirement (A) can be measured by the following method.

[0045] First, in order to eliminate the influence of the contact resistance between the conductive member and the measuring electrode, a low resistance film is deposited on the surface of the conductive member, the film is used as an electrode, and impedance is measured with two terminals using the conductive support as a ground electrode.

[0046] Examples of the method for forming the thin film include methods of forming a metal film such as metal vapor deposition, sputtering, coating of a metal paste, attaching a metal tape, etc. Among them, a method of forming a metal thin film such as a platinum film or a palladium film as an electrode by vapor deposition is preferred from the viewpoint of reducing the contact resistance with the conductive member.

[0047] When the metal thin film (electrode) is formed directly on the surface of the conductive member, it is preferred to provide a mechanism capable of grabbing the charging member to the vacuum vapor deposition device in view of simplicity and uniformity of the thin film. It is preferred to use a vacuum vapor deposition device further provided with a rotating mechanism for the conductive member having a cylindrical cross section.

[0048] For a cylindrical conductive member whose cross section is formed by a curved surface such as a circle, it may be difficult to connect the metal film serving as the above-mentioned measuring electrode to the impedance measuring device. Therefore, it is preferred to use the following method. Specifically, after a metal film electrode having a width of about 10 mm to 20 mm is formed in the length direction of the conductive member, a metal sheet is wound without a gap, the metal sheet is connected to the measuring electrode output from the measuring device, and then measurement can be performed. As a result, an electrical signal from the conductive layer of the conductive member can be appropriately obtained by the measuring device, and impedance measurement can be performed. When measuring impedance, the metal sheet can be a metal sheet having a resistance value equivalent to the metal part of the connecting cable of the measuring device, for example, aluminum foil or a metal strip can be used.

[0049] The impedance measuring device may be capable of measuring up to 1.0×10 7 Any device that measures impedance in a frequency region of Hz, such as an impedance analyzer, a network analyzer, or a spectrum analyzer. Among them, it is preferred to measure impedance from the resistance region of the conductive member by an impedance analyzer.

[0050] Figure 4A and Figure 4B FIG. 1 is a schematic diagram showing a state where a measuring electrode is formed on a conductive member. Figure 4A and Figure 4B In the figure, reference numeral 41 denotes a conductive support, reference numeral 42 denotes a conductive layer, reference numeral 43 denotes a platinum vapor-deposited layer as a measuring electrode, and reference numeral 44 denotes an aluminum sheet. Figure 4A It is a perspective view. Figure 4B is a cross-sectional view. Figure 4B As shown, it is important that the conductive layer 42 is sandwiched between the conductive support 41 and the conductive layer 43 of the measuring electrode.

[0051] Impedance measurement conditions will be described. Use an impedance measuring device (e.g., trade name "Solartron 1260", 96W dielectric impedance measurement system, manufactured by Solartron Metrology) to measure the impedance in a frequency region of 1.0Hz. The measurement is performed under an environment where the temperature is 23°C and the relative humidity is 50%. The amplitude of the AC voltage is 1Vpp. The conductive member is divided into five regions in five equal parts in the length direction, and the above-mentioned measurement is performed at any point in each region, i.e., a total of five points. Its arithmetic mean is taken as the impedance of the conductive member. The more specific process of the measurement will be described below.

[0052] Requirement (B)

[0053] The requirement (B) is a requirement indicating the relationship between the volume resistivity of the domain exposed on the outer surface of the conductive member and the thickness direction of the conductive layer.

[0054] Figure 5 is a schematic cross-sectional view of the vicinity of the outer surface of a conductive layer (surface layer) of an electrophotographic conductive member (hereinafter, also referred to as an electrophotographic roller) 500 having a roller shape according to an aspect of the present disclosure.

[0055] The conductive layer 501 of the electrophotographic roller 500 includes a matrix 503 and a plurality of domains 505 dispersed in the matrix 503. The domains 505 include a cross-linked product 505-1 of a second rubber and conductive particles 505-3. Figure 5 The support is not shown in the figure, but exists vertically below the conductive layer 501.

[0056] At least a portion of the domain 505-s among the plurality of domains 505 is exposed on the outer surface 500-1 of the electrophotographic roller 500. That is, the outer surface 500-1 of the electrophotographic roller 500 is composed of the matrix 503 and the exposed portion of the domain 505-s. The domain 505-s also includes a cross-linked product of the second rubber and conductive particles, but they are omitted for convenience of describing the configuration of the domain 505-s.

[0057] When the maximum length of the domain 505-s in the cross section of the conductive layer 501 in the thickness direction is Ld, the region with a thickness of 0.1×Ld on the side farthest from the support is the first region 505-s1. The region with a thickness of 0.1×Ld on the side closest to the support is the second region 505-s2. Figure 6 As shown, the domain 505 - s satisfies R1>R2, where R1 is the volume resistivity of the portion 601 of the first region 505 - s1 that is not a conductive particle, and R2 is the volume resistivity of the portion 602 of the second region that is not a conductive particle.

[0058] In the conductive layer, it is considered that electron conductivity is generated by electron transfer between the plurality of domain particles 505 from the support to the outer surface of the conductive layer, and finally discharge occurs from the domain 505-s exposed on the outer surface of the conductive member toward the electrophotographic photosensitive member. In this configuration, regarding charge transfer between the plurality of domain particles 505, when the volume resistivity of the domain is low, electrons can be efficiently transferred.

[0059] On the other hand, regarding the discharge of the domain 505-s exposed from the surface, when the volume resistivity of the domain is large, it is easy to suppress the discharge unevenness and the occurrence of fogging on the electrophotographic image. That is, from the viewpoint of more smoothly receiving the charge from the domain 505 buried in the elastic layer, the volume resistivity of the domain 505-s exposed on the outer surface is preferably low, and on the other hand, in order to suppress the discharge unevenness, the volume resistivity is preferably high. The domain that satisfies this contradictory relationship of volume resistivity is the domain 505-s according to the present disclosure. In the domain 505-s, the volume resistivity of the part other than the conductive particles in the domain, that is, the part of the cross-linked product of the second rubber, is high in the first region and low in the second region. The discharge unevenness from the domain 505-s can be suppressed by increasing the volume resistivity R1 of the part other than the conductive particles in the first region. By increasing the volume resistivity R2 of the part other than the conductive particles in the second region, the charge from the other domains 505 buried in the conductive layer can be effectively received.

[0060] In requirement (B), the meaning of measuring the volume resistivity of the portion other than the conductive particles of the domain is as follows. The portion other than the conductive particles of the domain is the resin portion in which the conductive particles are dispersed. The imparting of conductivity using an electronic conductive agent such as conductive particles is affected by the volume resistivity of the resin portion in which the electronic conductive agent is dispersed. Therefore, the degree of imparting conductivity can be evaluated by measuring the volume resistivity of the resin portion in which the conductive particles are dispersed.

[0061] In requirement (B), the meaning of measuring the volume resistivity of each of the first region and the second region is as follows. As described above, the region participating in discharge is the first region. It is considered that the region mainly participating in the electron transfer between the domain particle phases is mainly controlled by the second region. Therefore, by measuring each of the first region and the second region and controlling the relationship between R1 and R2, both suppression of discharge unevenness and charge transfer between domain particles can be achieved.

[0062] Volume resistivity R1 and volume resistivity R2 are measured as follows. A slice (thin slice) having a predetermined thickness (e.g., 1 μm) including a matrix-domain structure is cut out from the conductive layer. Examples of slicing methods include a sharp razor blade, a slicer, and a focused ion beam (FIB) method. In the present disclosure, a slicer is used. Next, the measurement can be performed by contacting a microprobe of a scanning probe microscope (SPM) or an atomic force microscope (AFM) with a portion other than the conductive particles of the domain exposed on the outer surface of the slice.

[0063] When a filler or the like other than the conductive particles is added to the domain, the portion other than the conductive particles and the filler is measured. The domain will be described in detail below.

[0064] The volume resistivity is measured as follows. First, one surface of a thin slice cut out from the conductive layer is grounded. Next, a microprobe (the tip of a cantilever) of a scanning probe microscope (SPM) or an atomic force microscope (AFM) is brought into contact with a portion of the surface of the domain opposite to the ground surface of the thin slice, and a DC voltage of 0.5 V is applied to obtain a current value image. The volume resistivity is calculated using the above current value image and the film thickness of the thin slice.

[0065] The values ​​of volume resistivity R1 and volume resistivity R2 of the cylindrical conductive member are determined as follows. The conductive layer is divided into five equal parts in the length direction and four equal parts in the circumferential direction, and thin slice samples are cut out one by one from each area. From each sample, the volume resistivity R1 and volume resistivity R2 are measured at a total of 60 positions for each of the three positions of the domain exposed on the surface using the above method, and the arithmetic mean is calculated.

[0066] The above-mentioned volume resistivity R1 and the above-mentioned volume resistivity R2 are not particularly limited, as long as R1>R2 is satisfied, but it is more preferred to satisfy R1 / R2≥3.0. When R1 / R2 is 3.0 or more, it is possible to suppress the discharge unevenness from the outer surface side while realizing the charge supply associated with the domain particles at the same time. The upper limit is not particularly limited, for example, it is preferred to satisfy 30.0≥R1 / R2≥3.0, and it is more preferred to satisfy 22.0≥R1 / R2≥3.0. When R1 / R2 is 30.0 or less, both the reception of charges from other domains and the discharge stability can be achieved at a higher level.

[0067] The following will describe a method for adjusting the volume resistivity R1 and the volume resistivity R2.

[0068] Will refer to Figure 1 The conductive member is described using a conductive roller as an example. Figure 1 1 is a cross-sectional view showing the structure of a cross section perpendicular to the longitudinal direction, that is, the axial direction of the conductive roller. The conductive roller includes a cylindrical support 11 having a conductive outer surface and a conductive layer 12 provided on the outer peripheral surface of the support 11, that is, the outer surface of the support. However, in the conductive member, the shape of the support is not particularly limited.

[0069] Support

[0070] The material for forming the support 11 can be appropriately selected and used from materials known in the field of electrophotographic conductive members and materials that can be used as conductive members. Examples thereof include metals or alloys such as aluminum, stainless steel, conductive synthetic resins, iron, and copper alloys.

[0071] In addition, these materials can be subjected to oxidation treatment or plating treatment using chromium or nickel, etc. As the type of plating, electroplating or chemical plating can be used. From the viewpoint of dimensional stability, chemical plating is preferred. The example of chemical plating used here includes nickel plating, copper plating, gold plating and various other alloy plating. Among them, chemical nickel plating is preferred.

[0072] The plating thickness is preferably 0.05 μm or more, and in consideration of the balance between working efficiency and rust prevention ability, the plating thickness is preferably 0.10 μm to 30.00 μm.

[0073] The cylindrical support 11 may have a solid cylindrical shape or a hollow cylindrical shape (cylindrical shape). The outer diameter of the support is preferably 3 mm to 10 mm. The length of the support in the longitudinal direction is not particularly limited, and is preferably 200 mm to 300 mm, for example.

[0074] Furthermore, if necessary, the support may be partially processed for mounting to an electrophotographic image forming apparatus.

[0075] When there is an intermediate resistance layer or an insulating layer between the support and the conductive layer, it may be difficult to quickly supply the charge after the charge is consumed by discharge. Therefore, it is preferred that the conductive layer is directly arranged in contact with the support. It is also preferred that an intermediate layer formed by inserting only a conductive resin layer such as a primer layer is provided on the outer surface of the support. The primer layer is more preferably a film. As a primer, a known primer can be selected and used according to the rubber material for forming the conductive layer and the material of the support. Examples of the material of the primer include thermosetting resins and thermoplastic resins, etc. Specifically, known materials such as phenolic resins, polyurethane resins, acrylic resins, polyester resins, polyether resins, and epoxy resins can be used. Among them, phenolic resins are preferred, for example, Metaloc U-20 (manufactured by TOYOKAGAKU KENKYUSHOCO., LTD.) can be used.

[0076] Conductive layer

[0077] The conductive layer includes a matrix including a crosslinked product of a first rubber and a plurality of domains dispersed in the matrix. The outer surface of the conductive layer is composed of the matrix and exposed portions of the domains exposed on the outer surface of the conductive layer. The outer surface of the conductive layer corresponds to the outer surface of the electrophotographic conductive member.

[0078] The shape of the domain is not particularly limited, and preferably, there are few convex and concave portions on the peripheral surface of the domain dispersed in the matrix. That is, the outer shape of the domain is preferably roughly spherical. When there are concavoconvex on the peripheral surface constituting the outline of the domain, the charge transfer between the domains may produce density, and the electron transfer from the support side of the conductive layer to the outer surface side of the conductive layer may become uneven. This is because, when there are concavoconvex on the peripheral surface of the domain, the charge transfer is concentrated on the convex portion, and the portion where the charge transfer is concentrated is partially formed, so that the portion where the charge transfer is insufficient may be generated at the same time. In addition, for the same reason, it is preferred that the ratio of the domain with a small number of convex and concave portions on the peripheral surface is high.

[0079] A small amount of convex and concave parts on the outer peripheral surface of the domain is specifically represented by an A / B value of 1.00 to 1.10, where the perimeter of the domain is A and the envelope perimeter of the domain is B. It can be said that there are few convex and concave parts on the outer peripheral surface of the outline of the domain with an A / B value in this range, that is, it is a smooth outer peripheral surface. The perimeter A of the domain and the envelope perimeter B of the domain are calculated by the following method by observation using an observation device such as an electron microscope. The value of A / B can be adjusted, for example, by reducing the domain diameter of the CMB or increasing the content of conductive particles in the domain.

[0080] In addition, the fact that the proportion of domains having a small number of convex and concave portions on the outer surface is high is specifically manifested by the fact that the number ratio of domains in which the value of A / B is 1.00 to 1.10 is 80% by number or more, wherein A is the perimeter of the domain and B is the envelope perimeter of the domain, and when a 15 μm square observation area is placed at three positions of the thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T for each of the cross-sections of the conductive layer in the thickness direction at a total of three positions (i.e., L1 / 4, L2 / 4, and L3 / 4) including the center of the conductive layer in the length direction and two positions of L / 4 from both ends of the conductive layer toward the center, the ratio is measured in the domains observed in each of all 9 observation areas, wherein L is the length in the length direction of the conductive layer and T is the thickness of the conductive layer. The number ratio of domains in which the value of A / B is 1.00 to 1.10 is more preferably 82% by number or more, and even more preferably 84% by number or more. The upper limit thereof is not particularly limited, and is, for example, preferably 80 to 100 number %, more preferably 82 to 100 number %, and still more preferably 84 to 100 number %.

[0081] The ratio of the number of domains where the A / B value is 1.00 to 1.10 can be controlled by the method described later.

[0082] The arithmetic mean value of A is preferably 0.30 to 16 μm, more preferably 1.2 to 9.5 μm.

[0083] Matrix

[0084] The matrix comprises a cross-linked product of a first rubber.

[0085] The volume resistivity ρm of the matrix is ​​preferably 1.0×10 8 to 1.0×10 17 Ω·cm. By setting the volume resistivity of the matrix to 1.0×10 8 Ω·cm or more, the matrix can prevent interference with charge transfer between domains. By setting the volume resistivity ρm to 1.0×10 17 When the charge bias is applied between the support and the member to be charged, discharge from the conductive member to the member to be charged can be smoothly performed.

[0086] The volume resistivity ρm of the matrix is ​​more preferably 1.0×10 10 to 1.0×10 17 Ω·cm, and more preferably 1.0×10 12 to 1.0×10 17 Ω·cm. The volume resistivity ρm of the matrix is ​​measured as follows. A slice (thin slice) having a predetermined thickness (e.g., 1 μm) including a matrix-domain structure is cut out from the conductive layer. Examples of slicing methods include a sharp razor blade, a slicer, and a focused ion beam (FIB) method. In the present disclosure, a slicer is used. Next, the volume resistivity can be measured by contacting a microprobe of a scanning probe microscope (SPM) or an atomic force microscope (AFM) with the matrix in the slice.

[0087] When a filler or the like is added to the matrix, the portion other than the filler is measured.

[0088] Specifically, the volume resistivity is measured as follows. First, one surface of a thin slice cut out from the conductive layer is grounded. Next, a microprobe (the front end of a cantilever) of a scanning probe microscope (SPM) or an atomic force microscope (AFM) is brought into contact with a portion of the surface of the substrate opposite to the ground surface of the thin slice, and a DC voltage of 0.5 V is applied to obtain a current value image. The volume resistivity is calculated using the above current value image and the film thickness of the thin slice.

[0089] The sampling positions of the sheet are a total of three positions (i.e., L1 / 4, L2 / 4, and L3 / 4) including the center of the conductive layer in the length direction and two positions L / 4 from both ends of the conductive layer toward the center, where L is the length of the conductive layer in the length direction. Next, the measurement positions are three positions in the matrix part of the thickness region from the outer surface of each sheet to a depth of 0.1T to 0.9T, i.e., a total of 9 positions, where T is the thickness of the conductive layer. The volume resistivity is measured at these measurement positions, and the arithmetic mean thereof is taken as the volume resistivity of the matrix.

[0090] The volume resistivity ρm of the matrix can be increased by using a non-polar rubber with a small solubility parameter value, such as natural rubber (NR), isoprene rubber (IR) or ethylene-propylene-diene terpolymer rubber (EPDM) as the first rubber. The volume resistivity ρm of the matrix can be reduced by using a polar rubber with a large solubility parameter value, such as chloroprene rubber (CR) or acrylonitrile-butadiene rubber (NBR).

[0091] First Rubber

[0092] The first rubber is the component with the largest blending ratio in the rubber composition for forming the conductive layer, and the first rubber dominates the mechanical strength of the conductive layer. Therefore, as the first rubber, a rubber showing the strength required for the electrophotographic conductive member is used in the conductive layer after crosslinking. Preferred examples of the first rubber include the following: natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene butadiene rubber (SBR), butyl rubber (IIR), ethylene-propylene rubber (EPM), ethylene-propylene-diene terpolymer rubber (EPDM), chloroprene rubber (CR), acrylonitrile-butadiene rubber (NBR), hydrogenated NBR (H-NBR) and silicone rubber.

[0093] The first rubber is more preferably at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR) and ethylene propylene diene rubber (EPDM), and is even more preferably at least one selected from the group consisting of styrene butadiene rubber (SBR) and acrylonitrile butadiene rubber (NBR).

[0094] The first rubber forming the matrix may contain a reinforcing material to such an extent that the conductivity is not affected. Examples of reinforcing materials include reinforcing carbon black having low conductivity. Specific examples of reinforcing carbon black include FEF, GPF, SRF, and MT carbon, etc.

[0095] In addition, as required, fillers such as calcium carbonate, processing aids such as zinc stearate, vulcanization aids, vulcanization accelerators such as tetrabenzylthiuram disulfide, tetramethylthiuram monosulfide, N-cyclohexyl-2-benzothiazolesulfenamide or 2-mercaptobenzimidazole, vulcanization accelerators such as zinc oxide, vulcanization retarder, antioxidant, softener, dispersant, colorant, and coarse particles, etc. can be added to the first rubber.

[0096] The SP value of the first rubber is not particularly limited, but is preferably 15.0 to 23.0, and more preferably 16.0 to 22.0. Within the above range, the absolute value of the difference in solubility parameter between the first rubber and the second rubber can be easily adjusted to the range described below.

[0097] domain

[0098] The domain contains a crosslinked product of the second rubber and conductive particles. Here, the conductivity of the conductive particles is less than 1.0×10 8 Volume resistivity of Ω·cm.

[0099] At least a portion of the plurality of domains is exposed on an outer surface of the electrophotographic conductive member.

[0100] When the impedance and volume resistivity ρm of the matrix according to the above requirement (A) are met, electrons are sequentially transferred between the plurality of domains from the conductive support, and finally electrons are emitted from the domains exposed on the surface of the conductive member, so that electronic conductivity is generated. Therefore, the domains are exposed on the outer surface in an amount that can obtain the effect of the present disclosure.

[0101] As described above, the requirements (A) and (B) are satisfied, so that the reverse fogging can be suppressed even when a low charging bias is applied.

[0102] Second Rubber

[0103] Specific examples of the second rubber preferably include at least one selected from the group consisting of natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), acrylonitrile-butadiene rubber (NBR), styrene-butadiene rubber (SBR), butyl rubber (IIR), ethylene-propylene rubber (EPM), ethylene-propylene-diene rubber (EPDM), chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (H-NBR), silicone rubber and polyurethane rubber (U).

[0104] The second rubber more preferably includes at least one selected from the group consisting of isoprene rubber (IR), butadiene rubber (BR), styrene butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR) and ethylene propylene diene rubber (EPDM), and further more preferably includes at least one selected from the group consisting of styrene butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR) and ethylene propylene diene rubber (EPDM). The second rubber is preferably different from the first rubber.

[0105] The SP value of the second rubber is not particularly limited, but is preferably 15.0 to 23.0, and more preferably 16.0 to 22.0. Within the above range, the absolute value of the difference in solubility parameter between the first rubber and the second rubber can be easily adjusted to the range described below.

[0106] Conductive particles

[0107] Examples of the conductive particles include particles having a conductive surface coated with a carbon material such as conductive carbon black or graphite, a conductive oxide such as titanium oxide or tin oxide, a metal such as Cu or Ag, or particles of a conductive oxide or metal. Two or more of these conductive particles may be appropriately blended and used.

[0108] In a domain observed in a cross section of the conductive layer in the thickness direction, the ratio S of the cross-sectional area of ​​the conductive particles contained in the domain to the cross-sectional area of ​​the domain is c / S is preferably 20.0 area % or more. By filling the domain with conductive particles at a high density in this way, it is easy to reduce the unevenness of the outer peripheral surface of the domain. S c The upper limit of / S is not particularly limited, but is preferably 35.0 area % or less. c / S is preferably 20.0 to 35.0 area %, 25.0 to 35.0 area %, or 26.0 to 33.0 area %.

[0109] In order to obtain a domain densely filled with conductive particles, conductive carbon black is preferably used as the conductive particles. That is, the conductive particles preferably contain carbon black. For example, the carbon black is preferably at least one selected from the group consisting of gas furnace black, oil furnace black, thermal black, lamp black, acetylene black and Ketjen black.

[0110] Among them, it is particularly preferable to use a DBP absorption of 40 to 80 cm 3 / 100g of carbon black. DBP absorption (cm 3 / 100g) is the volume of dibutyl phthalate (DBP) that can absorb 100g of carbon black, and is measured according to Japanese Industrial Standard (JIS) K6217-4:2017 (Carbon black for rubber - Basic properties - Part 4: Determination of oil absorption (including compression test specimens)). Generally, carbon black has a tufted higher order structure in which primary particles with an average particle size of 10nm to 50nm are aggregated. The tufted higher order structure is called structure, and its degree is measured by DBP absorption (cm 3 / 100g) to quantify.

[0111] Generally, carbon black having a developed structure has high reinforcing properties for rubber, is difficult to introduce into rubber, and has a significantly high shear torque during kneading. Therefore, it is difficult to increase the filling amount in the domain.

[0112] On the other hand, the conductive carbon black having a DBP absorption within the above range has an underdeveloped structure, so the carbon black is less aggregated and has excellent dispersibility in rubber. Therefore, the filling amount in the domain can be increased, and as a result, the outer shape of the domain closer to a spherical shape can be easily obtained.

[0113] In addition, in carbon black with a developed structure, carbon black easily aggregates with each other, and the aggregate easily becomes a lump with a large concavoconvex structure. On the other hand, conductive carbon black having a DBP absorption within the above range is preferably used to obtain a domain with few concavoconvexities on the outer peripheral surface because it is difficult to form an aggregate. The content of conductive particles such as conductive carbon black is preferably 20 to 150 parts by mass relative to 100 parts by mass of the second rubber contained in the domain. The content is more preferably 50 to 100 parts by mass.

[0114] The volume resistivity of the domain is preferably 1.0×10 4 Ω·cm or less. When the volume resistivity of the domain is 1.0×10 4 When the volume resistivity of the domain is less than 1.0×10·cm, the domain is easily conductive even at a volume fraction of the domain that stably forms the matrix-domain structure. The lower limit of the volume resistivity of the domain is not particularly limited, and may be, for example, 1.0×10 1 to 1.0×10 4 Ω·cm, or 5.0×10 1 to 1.0×10 4 Ω·cm.

[0115] The measurement of the volume resistivity of the domains was performed in the same manner as the measurement of the volume resistivity of the matrix described above, except that the measurement was performed at positions corresponding to the domains of the ultrathin sheets.

[0116] Method for manufacturing conductive layer

[0117] The conductive layer of the conductive member can be formed, for example, by a method comprising the following steps (i) to (iv):

[0118] Step (i): preparing a domain-forming rubber composition (hereinafter, also referred to as “CMB”) containing conductive particles and a second rubber;

[0119] Step (ii): preparing a matrix-forming rubber composition (hereinafter, also referred to as "MRC") containing a first rubber;

[0120] step (iii): kneading CMB and MRC to prepare a rubber composition for forming a conductive layer having a matrix-domain structure; and

[0121] Step (iv): forming a layer of the rubber composition for forming a conductive layer prepared in step (iii) on a support directly or via other layers, and curing the layer of the rubber composition to form a conductive layer.

[0122] The mixing ratio of CMB to MRC (CMB:MRC) in the rubber composition for forming the conductive layer is preferably 10:90 to 40:60, more preferably 20:80 to 30:70. The rubber composition for forming the conductive layer may contain known additives such as a vulcanizing agent and a vulcanization accelerator as required. The conductive layer is, for example, a crosslinked product (vulcanized product) of the rubber composition for forming the conductive layer.

[0123] Then, as conductive particles for preparing CMB, a large amount of DBP absorption preferably 40 to 170 cm 3 / 100g, more preferably 40 to 90cm 3 It is effective to prepare CMB by kneading the mixture with carbon black of 100 g / 100 g. In this case, the blending amount of carbon black in CMB relative to the second rubber is preferably 40 to 200 parts by mass, for example, relative to 100 parts by mass of the second rubber. The blending amount is particularly preferably 50 to 100 parts by mass.

[0124] The ratio S of the cross-sectional area of ​​the conductive particles contained in the domain to the cross-sectional area of ​​the domain can be measured as follows: c First, a thin sheet of a conductive layer is prepared. In order to preferentially observe the matrix-domain structure, a pretreatment such as a dyeing treatment or a vapor deposition treatment may be performed to preferentially obtain a contrast between a conductive phase and an insulating phase.

[0125] The thin slice subjected to fracture surface formation and pretreatment can be observed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM). Among them, from the viewpoint of the quantification accuracy of the area of ​​the domain as the conductive phase, it is preferred to observe with a magnification of 1,000 to 100,000 using SEM. The obtained observed image is binarized and analyzed using an image analysis device or the like to obtain the above ratio. The specific method will be described below.

[0126] In order to further reduce the electric field concentration between domains, it is preferred to make the outer shape of the domain closer to a sphere. Examples of the above method include the following method: in the step of preparing a rubber composition in which a domain of CMB is formed in a matrix of MRC, the domain diameter of CMB is controlled to be small by kneading MRC and CMB to separate MRC and CMB. When the domain diameter of CMB decreases, the total specific surface area of ​​CMB increases, and the interface with the matrix increases, so that the tension for reducing tension acts on the interface of the domain of CMB. As a result, the outer shape of the domain of CMB is closer to a sphere.

[0127] Here, it is known that Taylor's formula (Formula (1)), Wu's empirical formula (Formulas (2) and (3)), and Tokita's formula (Formula (4)) are factors that determine the domain diameter D in the matrix-domain structure formed when two incompatible polymers are melt-kneaded. (Sumitomo Chemical Co., Ltd., Technical Journal, 2003-II, 42)

[0128] Taylor formula

[0129] D = [C·σ / ηm·γ]·f(ηm / ηd) (1)

[0130] Wu's empirical formula

[0131] γ·D·ηm / σ = 4(ηd / ηm) 0.84 ·ηd / ηm > 1 (2)

[0132] γ·D·ηm / σ = 4(ηd / ηm) -0.84 ·ηd / ηm < 1 (3)

[0133] ·Tokita formula

[0134]

[0135] In equations (1) to (4), D represents the domain diameter of CMB (maximum Feret diameter Df), C represents a constant, σ represents interfacial tension, ηm represents the viscosity of the matrix, and ηd represents the viscosity of the domain. In equation (4), γ represents the shear rate, η represents the viscosity of the mixed system, and P represents the collision coalescence probability. represents the domain phase volume, and EDK represents the domain phase cutting energy.

[0136] From the above formulas (1) to (4), in order to reduce the domain diameter D of CMB, for example, it is effective to control the physical properties of CMB and MRC and the kneading conditions in step (iii). Specifically, it is effective to control the following four items (a) to (d):

[0137] (a) The difference in interfacial tension σ between CMB and MRC;

[0138] (b) The ratio of the viscosity of CMB (ηd) to the viscosity of MRC (ηm) (ηm / ηd);

[0139] (c) in step (iii), the shear rate (γ) during kneading of the CMB and the MRC and the energy during shearing (EDK); and

[0140] (d) The volume fraction of CMB relative to the kneaded product of CMB and MRC in step (iii).

[0141] (a) Difference in interfacial tension between CMB and MRC

[0142] Generally, when two incompatible rubbers are mixed, phase separation occurs. This is because the interaction between the same polymers is stronger than the interaction between different polymers, so the same polymers aggregate with each other, and the free energy is reduced and stabilized. Since the interface of the phase separation structure is in contact with different polymers, the free energy is higher than the free energy of the interior stabilized by the interaction between the same molecules. As a result, in order to reduce the free energy of the interface, interfacial tension is generated to reduce the area of ​​contact with different polymers. In the case of low interfacial tension, in order to increase entropy, even different polymers tend to mix more uniformly. The state of uniform mixing is dissolution, and the SP value and interfacial tension, which are measures of solubility, tend to be associated with each other. That is, it is believed that the difference in interfacial tension between CMB and MRC is related to the difference in SP value between CMB and MRC. Therefore, the interfacial tension difference can be controlled by the combination of MRC and CMB, especially the combination of the first rubber and the second rubber.

[0143] The combination of the first rubber in the MRC and the second rubber in the CMB is preferably set so that the absolute value of the difference in solubility parameter (SP value) between the first rubber and the second rubber is 0.4 to 5.7 (J / cm 3 ) 0.5 The combination is more preferably set so that the absolute value of the difference in SP value is 0.4 to 5.0 (J / cm 3 ) 0.5 It is more preferable to set the absolute value of the difference in SP value to be 0.4 to 4.7 (J / cm 3 ) 0.5 It is particularly preferred to set the absolute value of the difference in SP value to be 0.4 to 3.2 (J / cm 3 ) 0.5 The absolute value of the difference in SP value is preferably set to be 0.4 to 1.0 (J / cm 3 ) 0.5 .

[0144] By using a rubber combination having an absolute value of the difference in SP values ​​within the above range, a phase separation structure can be formed more stably, and the domain diameter D of CMB can be reduced.

[0145] SP value of the first rubber (J / cm 3 ) 0.5 It is preferably 16.0 to 22.0, more preferably 17.0 to 21.7.

[0146] SP value of the second rubber (J / cm3 ) 0.5 It is preferably 16.0 to 22.0, more preferably 16.0 to 20.0.

[0147] Examples of preferred combinations of the first rubber and the second rubber include the combinations shown in Table 1, provided that the absolute value of the difference in SP value is within the above range.

[0148] [Table 1]

[0149] First Rubber Second Rubber SBR NBR N B SBR N B BR EPDM NBR EPDM SBR IR SBR BR NBR SBR EPDM SBR IR

[0150] SP value measurement method

[0151] The SP values ​​of the first rubber and the second rubber respectively included in the MRC and the CMB can be accurately calculated by preparing a calibration curve using a material with a known SP value. As the known SP value, a catalog value of a material manufacturer can also be used.

[0152] For example, the SP value of each of NBR and SBR is almost determined by the content ratio of acrylonitrile or styrene, and does not depend on the molecular weight. Therefore, in the rubber constituting the matrix and the domain, the content ratio of acrylonitrile or styrene is analyzed using analytical methods such as pyrolysis gas chromatography (Py-GC) and solid-state NMR. Then, based on the content ratio from the calibration curve obtained from the material with known SP value, the SP value can be calculated.

[0153] The SP value of isoprene rubber is determined by the isomeric structure of 1,2-polyisoprene, 1,3-polyisoprene, 3,4-polyisoprene, cis-1,4-polyisoprene or trans-1,4-polyisoprene, etc. Therefore, similarly to SBR and NBR, the isomer content ratio is analyzed by Py-GC or solid-state NMR, and the SP value can be calculated from a material whose SP value is known.

[0154] The SP value of a material whose SP value is known is obtained by the Hansen sphere method.

[0155] (b) Viscosity ratio between CMB and MRC

[0156] As the viscosity ratio (ηd / ηm) between CMB and MRC approaches 1, the maximum Feret diameter of the domain can be made smaller. The viscosity ratio between CMB and MRC can be adjusted by selecting the Mooney viscosity of each of CMB and MRC and the type and amount of blended fillers. Plasticizers such as paraffin oil can also be added to such an extent that the formation of the phase separation structure is not hindered. The viscosity ratio can be adjusted by adjusting the temperature during kneading. The viscosity of CMB or MRC can be measured according to JIS K6300-1:2013 by measuring the Mooney viscosity ML at the rubber temperature during kneading. (1+4) Come get.

[0157] (c) Shear rate during kneading of MRC and CMB and energy during shearing

[0158] As the shear rate during the kneading of MRC and CMB is higher and the energy during shearing is greater, the maximum Feret diameter Df of the domain can be made smaller.

[0159] The shear rate can be increased by increasing the inner diameter of a stirring member such as a blade or screw of a kneader, reducing the gap between the end surface of the stirring member and the inner wall of the kneader, or increasing the rotation speed. The energy during shearing can be increased by increasing the rotation speed of the stirring member or increasing the viscosity of the first rubber in the CMB and the second rubber in the MRC.

[0160] (d) Volume fraction of domains (volume fraction of CMB relative to the kneaded product of CMB and MRC)

[0161] The volume fraction of CMB relative to the kneaded product of CMB and MRC is related to the collision-coagulation probability of CMB to MRC. Specifically, when the volume fraction of CMB relative to the kneaded product of CMB and MRC decreases, the collision-coagulation probability between CMB and MRC decreases. That is, the size of the domain can be reduced by reducing the volume fraction of the domain in the conductive layer within the range in which the desired conductivity can be obtained.

[0162] Methods for Confirming Matrix-Domain (MD) Structure

[0163] The matrix-domain structure can be confirmed, for example, by the following method: That is, a thin slice of the conductive layer is cut out from the conductive layer to prepare an observation sample. Examples of a unit for cutting a thin slice include a razor blade, a microtome, and a FIB.

[0164] If necessary, the observation sample is subjected to a treatment that can help distinguish the matrix and the domain (such as a dyeing treatment and a vapor deposition treatment). Then, the observation sample is observed using a laser microscope, SEM or TEM. A more specific process will be described below.

[0165] Methods for measuring the perimeter and envelope perimeter of a domain, the number of domains and the average number of domains

[0166] The perimeter and envelope perimeter of a domain as well as the number and average number of domains can be measured, for example, as follows.

[0167] First, prepare sheet by the same method as the measurement of the volume resistivity of the above-mentioned matrix. Subsequently, thin slices with fracture surface can be formed by methods such as following freezing fracture method (lower freezing fracture method), cross polisher method or focused ion beam (FIB) method. Considering the smoothness of fracture surface and the pretreatment of observation, FIB method is preferred. In order to preferentially observe matrix-domain structure, pretreatments such as dyeing treatment or vapor deposition treatment can be carried out to preferentially obtain the contrast between conductive phase and insulating phase.

[0168] The slice subjected to fracture surface formation and pretreatment can be observed by SEM or TEM. However, from the viewpoint of accurate quantification of the perimeter of the domain and the perimeter of the envelope, it is preferable to observe by SEM at a magnification of 1,000 to 100,000.

[0169] The perimeter and envelope perimeter of the domain and the number of domains can be measured by quantizing the captured images as described above. The fracture surface images obtained by SEM observation are scaled by 8-bit grayscale using image processing software such as trade name: Image-Pro Plus (manufactured by Planetron) to obtain a monochrome image with 256 grayscale levels. Next, the black and white of the image is inverted so that the domains in the fracture surface become white and are binarized. Next, the perimeter, envelope perimeter and number of domains can be calculated from each domain group in the image. A more specific method will be described below.

[0170] For the above measurement, slices are cut from the sample at a total of three positions (i.e., L1 / 4, L2 / 4, and L3 / 4) including the center of the conductive layer in the length direction and two positions from both ends of the conductive layer toward the center L / 4, where L is the length of the conductive layer of the conductive member in the length direction. The direction in which the slice is cut is the direction of providing a cross section perpendicular to the length direction of the conductive layer. Regarding the observation position of each slice section, when a 15 μm square observation area is placed at 3 positions in the thickness area from the outer surface of each slice to a depth of 0.1T to 0.9T (where T is the thickness of the conductive layer), measurements can be performed in a total of 9 observation areas. The arithmetic mean of the measured values ​​obtained in the 9 observation areas is taken as the measurement result.

[0171] How to implement requirement (B)

[0172] The method for achieving the above requirement (B) is not particularly limited as long as the volume resistivity R1 and the volume resistivity R2 satisfy R1>R2. Specific examples of the method include an immersion treatment, a method of adding a surface-transferred material to a conductive layer-forming material, and the like. More specifically, an immersion treatment that can increase the resistance only near the outer surface of the conductive layer is preferred.

[0173] The impregnation treatment is a treatment in which a monomer is impregnated from the surface of a conductive layer precursor such as a conductive resin layer, and then the monomer is cured. A resin that is a cured product of a monomer is also referred to as a curable resin.

[0174] By performing the impregnation treatment, the curable resin is present in the gap between the rubber constituting the matrix and the domain forming the surface of the conductive layer. As a result, the distance between the conductive particles present in the domain is widened by the curable resin, and the resistance increases. In addition, since the curable resin generally has a high volume resistivity, the resin portion constituting the matrix also has a high resistance. In addition, since a network derived from the curable resin is formed in the rubber, the ionic conductivity derived from the impurities contained in the rubber is also reduced. Therefore, it is believed that the volume resistivity of the rubber increases. That is, the volume resistivity R1 of the portion other than the conductive particles in the first region tends to be larger than the volume resistivity R2 of the portion other than the conductive particles in the second region.

[0175] From the above-mentioned effects, the above-mentioned requirement (B) can be achieved by performing an immersion treatment on a conductive layer having a matrix-domain structure in which domains containing a cross-linked product of the second rubber and conductive particles are dispersed in a matrix containing a cross-linked product of the first rubber and the domains are exposed on the surface.

[0176] In addition, the immersion treatment reduces the dirt adhesion of the surface of the conductive member in addition to achieving requirement (B). Although the reason is not clear, it is believed that the presence of a curable resin in the gaps between the rubber constituting the matrix and the domain changes the surface properties of the conductive layer and reduces the adhesion of dirt components such as developers and external additives present on the surface of the photosensitive member.

[0177] The method of the immersion treatment is not particularly limited, and examples thereof include spraying, dipping (dip coating) and roller coating using a coating obtained by adding a solvent to a raw material. The dip coating method is preferred because it is simple and excellent in production stability. In order to polymerize the monomer after coating, additional treatment such as heating or light irradiation is preferably performed as needed.

[0178] The impregnation area of ​​the conductive layer can be controlled by the type of monomer to be impregnated, the type of solvent used to dissolve the monomer, the monomer concentration, the impregnation time, and the like.

[0179] In order to suppress discharge unevenness from the outer surface of the conductive member and simultaneously supply charge between the domain particle phases, the region to be impregnated is preferably a region that is closer to the outer surface of the conductive member than the second region. That is, the second region is preferably not impregnated.

[0180] When the impregnation treatment is performed using rubber and a monomer that does not react or hardly reacts, it is considered that an interpenetrating polymer network is formed. Hereinafter, the interpenetrating polymer network may be referred to as an "IPN network". Since the cross-linked rubber constituting the IPN network has substantially no chemical bond with the curable resin, it is easy to maintain rubber elasticity, which is more preferred. That is, the curable resin more preferably forms an interpenetrating polymer network together with the first rubber and the second rubber.

[0181] IPN network confirmation method

[0182] Examples of methods for confirming the formation of an IPN network include a method for confirming by a scanning electron microscope (SEM) or a transmission electron microscope (TEM), a method for confirming by solvent extraction, and a method for confirming by shifting the glass transition point before and after the formation of the IPN network. In the present disclosure, confirmation is performed by a transmission electron microscope (TEM). The specific method will be described below.

[0183] That is, a thin slice of the conductive layer is cut out from the conductive layer to prepare an observation sample. Examples of the slicing method include a sharp razor blade, a microtome, and a focused ion beam (FIB) method.

[0184] If necessary, the observation sample is subjected to a treatment that can help distinguish the rubber from the curable resin (for example, dyeing treatment and vapor deposition treatment), and then observed by TEM.

[0185] Among them, from the viewpoint of accuracy, it is preferred to observe using a TEM at a magnification of 1,000 to 100,000.

[0186] monomer

[0187] As the monomer used for the immersion treatment, in order to form a crosslinked structure, it is preferable to use a multifunctional monomer including a plurality of functional groups having curability. In addition, a monofunctional monomer may be used in combination as necessary.

[0188] Specific examples of monomers used for the immersion treatment include acrylates, methacrylates, vinyl ethers, epoxides, and isocyanates. Among them, (meth)acrylates are preferred from the viewpoint of high reactivity and high insulation. (Meth)acrylates refer to acrylates or methacrylates.

[0189] The (meth)acrylic acid ester is selected from commonly used known esters, and examples thereof include the following:

[0190] Such as diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, PO modified neopentyl glycol di(meth)acrylate or polyethylene glycol di(meth)acrylate, etc., difunctional (meth)acrylates such as trimethylolpropane ethoxy tri(meth)acrylate or glycerol propoxy tri(meth)acrylate, etc., tetrafunctional (meth)acrylates such as pentaerythritol tetra(meth)acrylate, pentaerythritol tetraethoxy (meth)acrylate or trimethylolpropane tetra(meth)acrylate. Among them, at least one selected from the group consisting of PO modified neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate and pentaerythritol tetra(meth)acrylate is preferred.

[0191] The vinyl ether monomer is selected from commonly used known monomers, and examples thereof include the following: bifunctional vinyl ethers such as 1,4-butanediol divinyl ether or cyclohexanedimethanol divinyl ether, among which cyclohexanedimethanol divinyl ether is preferred.

[0192] The epoxide monomer is selected from commonly used known monomers, and examples thereof include the following: bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, and resorcinol diglycidyl ether. Among them, hydrogenated bisphenol A diglycidyl ether is preferred.

[0193] The isocyanate monomer is selected from commonly used known monomers, and examples thereof include the following: toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric diphenylmethane polyisocyanate, polymeric polyphenylene polyisocyanate, hydrogenated MDI, xylene diisocyanate (XDI), hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI). Among them, at least one selected from the group consisting of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric diphenylmethane polyisocyanate and polymeric polyphenylene polyisocyanate is preferred, and polymeric polyphenylene polyisocyanate is more preferred.

[0194] The monomers can be confirmed by using infrared spectroscopy (IR) or pyrolysis gas chromatography-mass spectrometry (Pyr-GCMS).

[0195] As the polymerization method of the above-mentioned monomers, a known method can be used. Specific examples thereof include thermal polymerization by heating, photopolymerization such as irradiation with ultraviolet rays, etc. For each polymerization method, a known free radical polymerization initiator or ion polymerization initiator can be used. Examples of thermal polymerization initiators in the case of thermal polymerization include peroxides such as 3-hydroxy-1,1-dimethylbutyl peroxyneodecanoate, α-cumyl peroxyneodecanoate, tert-butyl peroxyneoheptanoate, tert-butyl peroxypivalate, tert-amyl peroxyn-octanoate, 2-ethylhexyl tert-butylperoxycarbonate, dicumyl peroxide, di-tert-butyl peroxide, di-tert-amyl peroxide, 1,1-di(tert-butylperoxy)cyclohexane and 4,4-di(tert-butylperoxy)butyl valerate; and

[0196] Azo compounds, for example 2,2-azobisbutyronitrile, 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-methylbutyronitrile), 1,1-azobis(cyclohexane-1-carbonitrile), 2,2-azobis[2-(2-imidazolin-2-yl)propane], 2,2-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2-azobis(N-butyl-2-methoxypropionamide] and 2,2-azobis(isobutyric acid) dimethyl ester.

[0197] Examples of the photoradical generator in the case of photopolymerization by irradiation with ultraviolet rays include 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxycyclohexylphenylketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl} -2-methylpropan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0198] Examples of the photocationic polymerization initiator in the case of photopolymerization by irradiation with ultraviolet rays include 4-methylphenyl-4-(2-methylpropyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(2-methylpropyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(2-methylpropyl)phenyliodonium tetrafluoroborate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, bis[4-(diphenylsulfonio)phenyl]sulfide bishexafluorophosphate, tetraphenylphosphonium hexafluorophosphate, tetraphenylphosphonium hexafluoroantimonate, and tetraphenylphosphonium tetrafluoroborate.

[0199] These polymerization initiators may be used alone or in combination of two or more thereof.

[0200] From the viewpoint of efficiently proceeding the reaction, the blending amount of the polymerization initiator is preferably 0.5 to 10 parts by mass based on 100 parts by mass of the total amount of the specific resin-forming compound such as the above-mentioned monomer (eg, a compound having a (meth)acryloyl group).

[0201] As the heating device and the ultraviolet irradiation device, known devices can be used appropriately. As the light source for emitting ultraviolet rays, for example, an LED lamp, a high-pressure mercury lamp, a metal halide lamp, a xenon lamp or a low-pressure mercury lamp can be used. The cumulative light amount required during the polymerization can be appropriately adjusted according to the type and addition amount of the compound and polymerization initiator used.

[0202] The domain exposed on the outer surface of the conductive member preferably further comprises at least one resin selected from the group consisting of (meth) acrylic resin, epoxy resin, vinyl ether resin and urea-formaldehyde resin. Among them, (meth) acrylic resin is more preferred. For example, when the above-mentioned monomer is used in the above-mentioned impregnation treatment, the resin can be included in the domain. For example, (meth) acrylic resin is a polymer of (meth) acrylate, epoxy resin is a polymer of epoxide, vinyl ether resin is a polymer of vinyl ether, and urea-formaldehyde resin is a polymer of isocyanate and amine.

[0203] As described above, the resin preferably forms an interpenetrating polymer network together with the first rubber and the second rubber.

[0204] The first region preferably further comprises at least one resin selected from the group consisting of (meth) acrylic resin, epoxy resin, vinyl ether resin and urea-formaldehyde resin. Among them, (meth) acrylic resin is more preferred. For example, when the above-mentioned monomer is used in the above-mentioned impregnation treatment, the resin may be included in the first region.

[0205] As described above, the resin preferably forms an interpenetrating polymer network together with the first rubber and the second rubber.

[0206] In addition, it is preferred that the second region does not contain resin. This makes it easier to achieve requirement (B). Examples of methods for not allowing the resin to be contained in the second region include changing the composition of the dipping coating and changing the dipping time. The second region can be confirmed to be free of resin by the following method.

[0207] Processing box

[0208] At least one aspect of the present disclosure provides a process cartridge including the electrophotographic conductive member of the present disclosure. Figure 2 1 is a schematic cross-sectional view of an electrophotographic process cartridge 100 including a conductive member according to an embodiment of the present disclosure as a charging roller. The process cartridge is configured to integrate a developing device and a charging device and is detachably mounted to a main body of an electrophotographic image forming apparatus.

[0209] The developing device is formed by integrating at least a developing roller 103 , a toner container 106 , and a toner 109 , and may include a toner supplying roller 104 , a developing blade 108 , and a stirring blade 110 , as necessary.

[0210] The charging device is formed by integrating at least the photosensitive drum 101 and the charging roller 102, and may include a cleaning blade 105 and a waste toner container 107. A voltage is applied to each of the charging roller 102, the developing roller 103, the toner supplying roller 104, and the developing blade 108.

[0211] The conductive member according to the present disclosure may be used as a charging roller, a developing roller, a developing blade, or a toner supplying roller. The conductive member is preferably a charging member, and the conductive member is more preferably a charging roller.

[0212] Electrophotographic image forming apparatus

[0213] At least one aspect of the present disclosure provides an electrophotographic image forming apparatus including the electrophotographic member of the present disclosure. Figure 31 is a schematic configuration diagram of an electrophotographic image forming apparatus 200 using a conductive member according to an embodiment of the present disclosure as a charging roller. The apparatus is a color electrophotographic apparatus to which a process cartridge 100 is detachably mounted. In each process cartridge, toners of corresponding colors of black BK, magenta M, yellow Y, and cyan C are used.

[0214] The photosensitive drum 201 rotates in the direction of the arrow, is uniformly charged by the charging roller 202 to which a voltage is applied from a charging bias power source, and an electrostatic latent image is formed on its surface by exposure light 211. On the other hand, the toner 209 stored in the toner container 206 is supplied to the toner supply roller 204 by the stirring blade 210, and is conveyed to the developing roller 203. Then, the surface of the developing roller 203 is uniformly coated with the toner 209 by the developing blade 208 provided in contact with the developing roller 203, and electric charge is applied to the toner 209 by friction charging. The above-mentioned electrostatic latent image is developed by applying the toner 209 conveyed by the developing roller 203 provided in contact with the photosensitive drum 201, and is visualized as a toner image.

[0215] The visualized toner image on the photosensitive drum is transferred to the intermediate transfer belt 215 supported and driven by the tension roller 213 and the intermediate transfer belt driving roller 214 by the primary transfer roller 212 to which a voltage is applied by the primary transfer bias power supply. The toner images of the respective colors are sequentially superimposed to form a color image on the intermediate transfer belt.

[0216] The transfer material 219 is fed into the apparatus by a paper feed roller and conveyed between the intermediate transfer belt 215 and the secondary transfer roller 216. A voltage is applied to the secondary transfer roller 216 from a secondary transfer bias power source, and the secondary transfer roller transfers the color image on the intermediate transfer belt 215 onto the transfer material 219. The transfer material 219 to which the color image is transferred is subjected to a fixing process by the fixing unit 218 and is discharged to the outside of the apparatus, and the printing operation is terminated.

[0217] On the other hand, the toner remaining on the photosensitive drum and not transferred is scraped off by the cleaning blade 205 and stored in the waste toner storage container 207, and the above process is repeated for the cleaned photosensitive drum 201. The toner remaining on the primary transfer belt and not transferred is also scraped off by the cleaning device 217.

[0218] Although a color electrophotographic apparatus is shown as an example, in a monochrome electrophotographic apparatus (not shown), the process cartridge is a product that uses only black toner. A monochrome image is formed directly on a transfer material through a process cartridge and a primary transfer roller (without a secondary transfer roller) without using an intermediate transfer belt. Thereafter, the paper is fixed by a fixing unit and discharged to the outside of the apparatus, thereby terminating the printing operation.

[0219] Example

[0220] Hereinafter, the present disclosure will be described based on embodiments, but the technical scope of the present disclosure is not limited thereto.

[0221] Hereinafter, the charging member in the present disclosure was manufactured using the following materials.

[0222] Elastic layer forming material

[0223] NBR

[0224] NBR (1) (trade name: JSR NBR N230SV, acrylonitrile content: 35%, Mooney viscosity ML (1+4) 100℃: 32, SP value: 20.0(J / cm 3 ) 0.5 , manufactured by JSR Corporation, referred to as: N230SV)

[0225] NBR (2) (trade name: Nipol DN401LL, acrylonitrile content: 18.0%, Mooney viscosity ML (1+4) 100℃: 32, SP value: 17.4(J / cm 3 ) 0.5 , manufactured by Zeon Corporation, referred to as: DN401LL)

[0226] NBR (3) (trade name: JSR NBR N215SL, acrylonitrile content: 48%, Mooney viscosity ML (1+4) 100℃: 45, SP value: 21.7(J / cm 3 ) 0.5 , manufactured by JSR Corporation, referred to as: N215SL)

[0227] SBR

[0228] SBR (1) (trade name: Tufdene 2000R, styrene content: 25%, Mooney viscosity ML (1+4) 100℃: 45, SP value: 17.0(J / cm 3 ) 0.5 , manufactured by Asahi Kasei Corporation, referred to as: T2000R)

[0229] SBR (2) (trade name: Tufdene 2003, styrene content: 25%, Mooney viscosity ML (1+4) 100℃: 33, SP value: 17.0(J / cm 3 ) 0.5, manufactured by Asahi Kasei Corporation, referred to as: T2003)

[0230] EPDM

[0231] EPDM (trade name: Esprene505A, Mooney viscosity ML (1+4) 100℃: 47, SP value: 16.0(J / cm 3 ) 0.5 , manufactured by Sumitomo Chemical Co., Ltd., referred to as: E505A)

[0232] Butadiene rubber BR

[0233] Butadiene rubber (trade name: UBEPOL BR130B, Mooney viscosity ML (1+4) 100℃: 29, SP value: 16.8(J / cm 3 ) 0.5 , manufactured by UBE Corporation, referred to as: BR130B)

[0234] Isoprene rubber IR

[0235] Isoprene rubber (trade name: Nipol 2200L, Mooney viscosity ML (1+4) 100℃: 70, SP value: 16.5(J / cm 3 ) 0.5 , manufactured by Zeon Corporation, referred to as 2200L)

[0236] Epichlorohydrin rubber EO-EP-AGE ternary co-compound (GECO)

[0237] ·Epichlorohydrin rubber (trade name: EPICHLOMER CG102, Mooney viscosity ML (1+4) 100℃: 55, SP value: 18.5(J / cm 3 ) 0.5 , manufactured by OSAKASODACO., LTD., referred to as: CG102)

[0238] Conductive particles

[0239] Carbon black (1) (trade name: TOKABLACK #7270SB, DBP absorption: 62 cm 3 / 100g, manufactured by Tokai Carbon Co., Ltd., referred to as #7270)

[0240] Carbon black (2) (trade name: TOKABLACK #7360SB, DBP absorption: 87 cm 3 / 100g, manufactured by Tokai Carbon Co., Ltd., abbreviated as: #7360)

[0241] Carbon black (3) (trade name: Raven 1170, DBP absorption: 55 cm 3 / 100g, manufactured by Columbia Chemical Corporation, referred to as R1170)

[0242] Vulcanizing agent

[0243] Vulcanizing agent (trade name: SULFAX PMC, sulfur content 97.5%, manufactured by Tsurumi Chemical Industry Co., Ltd., referred to as sulfur)

[0244] Vulcanization accelerator

[0245] Vulcanization accelerator (1) (trade name: SANCELER TBZTD, tetrabenzylthiuram disulfide, manufactured by SANSHINCHEMICAL INDUSTRY CO., LTD., abbreviated as: TBzTD)

[0246] Vulcanization accelerator (2) (trade name: NOCCELER EP-60, vulcanization accelerator mixture, manufactured by OUCHI SHINKO CHEMICAL INDUSTRIAL CO., LTD., abbreviated as: EP-60)

[0247] Vulcanization accelerator (3) (trade name: NOCCELER TBT, tetrabutylthiuram disulfide, manufactured by OUCHI SHINKOCHEMICAL INDUSTRIAL CO., LTD., abbreviated as TBT)

[0248] Vulcanization accelerator (4) (trade name: NOCCELER TS, tetramethylthiuram monosulfide, manufactured by OUCHI SHINKOCHEMICAL INDUSTRIAL CO., LTD., abbreviated as TS)

[0249] Vulcanization accelerator (5) (trade name: ACCEL CZ, N-cyclohexyl-2-benzothiazolesulfenamide, manufactured by Kawaguchi Chemical Industry Co., Ltd., abbreviated as: Cz)

[0250] Vulcanization accelerator (6) (trade name: NOCRAC MB, 2-mercaptobenzimidazole, manufactured by OUCHI SHINKO CHEMICAL INDUSTRIAL CO., LTD., abbreviated as: MB)

[0251] filler

[0252] Filler (1) (trade name: NANOX #30, calcium carbonate, manufactured by MARUO CALCIUM CO., LTD., abbreviated as #30)

[0253] Filler (2) (Thermax flow foam N990, manufactured by CanCab Limited, referred to as MT)

[0254] Resin particles

[0255] PE particles (trade name: MIPELON XM-221U, polyethylene resin, average particle size: 25 μm, manufactured by Mitsui Chemicals, Inc., abbreviated as: PE)

[0256] Dipping treatment materials

[0257] monomer

[0258] Acrylic monomer 1 (trade name: EBECRYL 145, PO modified neopentyl glycol diacrylate, manufactured by DAICEL-ALLNEX LTD., abbreviated as: acrylic monomer 1)

[0259] Acrylic monomer 2 (trade name: A-TMPT, trimethylolpropane triacrylate, manufactured by SHIN-NAKAMURA CHEMICAL CO, LTD., abbreviated as: acrylic monomer 2)

[0260] Acrylic monomer 3 (trade name: PETIA, pentaerythritol (tri / tetra) acrylate, manufactured by DAICEL-ALLNEXL T., abbreviated as: acrylic monomer 3)

[0261] Vinyl ether monomer (trade name: CHDVE, cyclohexanedimethanol divinyl ether, NIPPON CARBIDEINDUSTRIES CO., INC., abbreviated as: vinyl ether)

[0262] Glycidyl ether monomer (trade name: DENACOL EX-252, hydrogenated bisphenol A diglycidyl ether, manufactured by NagaseChemteX Corporation, abbreviated as: epoxide)

[0263] Isocyanate monomer (trade name: Millionate MR-100, polymeric polyphenylene polyisocyanate, manufactured by Tosoh Corporation, abbreviated as: isocyanate)

[0264] Here, pentaerythritol (tri / tetra)acrylate refers to a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate.

[0265] Photopolymerization initiator

[0266] Photo radical polymerization initiator (trade name: Omnirad 127, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one, manufactured by IGM Resins BV, abbreviated as: radical)

[0267] Photocationic polymerization initiator (trade name: ADEKA ARKLS SP150, sulfonium salt-based photocationic polymerization initiator, manufactured by ADEKA Corporation, abbreviated as: cationic)

[0268] Example 1

[0269] Production of the conductive member 1

[0270] 1-1. Preparation of domain-forming rubber composition (CMB)

[0271] The materials of the types and amounts shown in Table 2 were mixed with a pressure kneader to obtain a domain-forming rubber composition (CMB). The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 18 minutes.

[0272] [Table 2]

[0273]

[0274] 1-2. Preparation of Matrix-Forming Rubber Composition (MRC)

[0275] The materials of the types and amounts shown in Table 3 were mixed with a pressure kneader to obtain a matrix-forming rubber composition (MRC). The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 18 minutes.

[0276] [Table 3]

[0277]

[0278] 1-3. Preparation of rubber composition 1 for forming conductive layer

[0279] The types and amounts of the respective materials shown in Table 4 were mixed with an open roll to prepare a conductive member-forming rubber composition 1. As a mixer, an open roll having a roll diameter of 12 inches was used. As mixing conditions, the front roll rotation speed was set to 10 rpm, the rear roll rotation speed was set to 8 rpm, left and right cut-back was performed 20 times in total at a roll gap of 2 mm, and then thin cutting was performed 10 times at a roll gap of 1.0 mm.

[0280] [Table 4]

[0281]

[0282] 1-4. Forming of Conductive Elastic Roller 1

[0283] A round bar having a total length of 244 mm and an outer diameter of 6 mm was prepared by subjecting the surface of free-cutting steel to chemical nickel plating. Next, an adhesive (trade name: Metaloc U-20, manufactured by TOYOKAGAKUKENKYUSHO CO., LTD.) was applied to the entire circumference of 222 mm excluding 11 mm at both ends of the round bar using a roll coater to prepare a support.

[0284] Next, a die having an inner diameter of 12.5 mm was attached to the front end of a crosshead extruder having a supply mechanism for a support and a discharge mechanism for an unvulcanized rubber roller, the temperature of the extruder and the crosshead was adjusted to 100° C., and the conveying speed of the conductive support was adjusted to 60 mm / sec. Under these conditions, the rubber composition for forming a conductive member was supplied from the extruder, and the outer peripheral portion of the support was coated with the rubber composition for forming a conductive member in the crosshead to obtain an unvulcanized rubber roller.

[0285] Next, the unvulcanized rubber roller was placed in a hot air vulcanizing furnace at 160° C. and heated for 60 minutes to vulcanize the layer of the unvulcanized rubber composition, thereby obtaining a roller having a conductive resin layer formed on the outer peripheral portion of the conductive support. Thereafter, both ends of the conductive resin layer were cut out by 10 mm to set the length of the conductive resin layer portion in the longitudinal direction to 224 mm.

[0286] Then, the surface of the conductive resin layer was ground with a rotating grindstone. As a result, a conductive elastic roller 1 having a diameter of 8.44 mm at a position of 90 mm from the center to both ends and a diameter of 8.5 mm at the center was manufactured.

[0287] 1-5. Preparation of Dipping Coating 1 and Production of Conductive Member 1

[0288] The materials of the types and amounts shown in Table 5 were mixed and dissolved to prepare an impregnation coating 1. The conductive elastic roller 1 was immersed in the impregnation coating 1 for 4 seconds to be impregnated with the acrylic monomer component. Thereafter, air drying was performed at room temperature for 30 minutes and drying was performed at 90° C. for 1 hour to volatilize the solvent. The dried conductive elastic roller 1 was irradiated with ultraviolet rays while rotating so that the cumulative light amount was 15,000 mJ / cm 2 The acrylic monomer was cured, thereby performing the immersion treatment. A high pressure mercury lamp (trade name: Handy type ultraviolet curing device, manufactured by Marionetwork) was used as an ultraviolet irradiation device. Thus, the conductive member 1 according to Example 1 was manufactured.

[0289] [Table 5]

[0290]

[0291] 2. Characteristic evaluation

[0292] 2-1. Impedance measurement

[0293] Impedance was measured by the following measurement method.

[0294] First, as a pretreatment, a deposited platinum film (electrode) with a thickness of 80 nm was formed on the outer surface of the charging roller as a conductive member while the charging roller was rotated. At this time, a masking tape was used to make an electrode with a width of 1.5 cm and uniform in the circumferential direction. By forming the electrode, the contribution of the contact area between the measuring electrode and the conductive member can be reduced as much as possible by the surface roughness of the conductive member. Next, an aluminum sheet was wound around the electrode without a gap to form Figure 4A and Figure 4B The measurement specimens shown.

[0295] Then, an impedance measuring device (trade name: Solartron 1260 96W, manufactured by Solartron Metrology) was connected from the aluminum sheet to the measuring electrode or support. Impedance was measured at a vibration voltage of 1 Vpp and a frequency of 1.0 Hz under an environment of a temperature of 23° C. and a relative humidity of 50% to obtain an absolute value of impedance.

[0296] The charging roller (length in the longitudinal direction: 224 mm) was divided into five regions in the longitudinal direction by five equal parts, and a measuring electrode was formed at any one point in each region, that is, at five points in total, and the above measurement was performed. The arithmetic mean value was taken as the impedance of the conductive member.

[0297] The impedance of the conductive member 1 is 5.8×10 6 The results are shown in Table 10.

[0298] 2-2. Measurement of the Perimeter and Envelope Perimeter of Domains and the Number of Domains in the Conductive Layer

[0299] The perimeter and envelope perimeter of the domain can be measured as follows. First, the conductive layer of the conductive member is cut into a sheet with a thickness of about 2 μm at a cutting temperature of -100°C using a microtome (trade name: Leica EM FCS, manufactured by Leica Microsystems GmbH). A sheet is cut from the sample at a total of three positions (i.e., L1 / 4, L2 / 4, L3 / 4) including the center of the conductive layer in the length direction and two positions from both ends of the conductive layer toward the center L / 4, where L is the length of the conductive layer of the conductive member 1 in the length direction. The direction of the cut sheet is the direction of providing a cross section perpendicular to the length direction of the conductive layer.

[0300] The sheet was used to deposit platinum on the cut flat surface. Next, a cross-sectional image was obtained by photographing at a magnification of 5,000 times using a scanning electron microscope (SEM) (trade name: S-4800, manufactured by Hitachi High-Tech Corporation). The obtained image was scaled by 8-bit grayscale using image processing software (trade name: ImageProPlus, manufactured by Media Cybernetics, Inc.) to obtain a monochrome image with a grayscale level of 256. Next, the monochrome image was inverted so that the domain in the monochrome image became white, and a binarization threshold was set for the brightness distribution of the image based on Otsu's discriminant analysis algorithm to obtain a binary image.

[0301] In the binary image, a 15 μm square area was cut out, and the perimeter and envelope perimeter were calculated using the counting function of the image processing software. The A / B value was calculated using the perimeter A and envelope perimeter B calculated for each domain observed in each observation area, and the proportion (number %) of domains with A / B values ​​of 1.00 to 1.10 in all observed domains was obtained. In addition, the arithmetic mean of A and the number of domains in the three observation areas were calculated from all observed domains.

[0302] Next, the observation position of each slice face will be described. When a 15 μm square observation area is placed at three positions in the thickness region from the outer surface of each slice to a depth of 0.1T to 0.9T or less, where T is the thickness of the conductive layer, A and B are measured in a total of 9 observation areas, and the arithmetic mean of the A / B value is calculated using the values ​​of A and B at these 9 positions and defined as A / B.

[0303] The ratio of the region where the A / B value in the conductive member 1 was 1.00 to 1.10 was 85%, and the arithmetic mean of the A / B value was 1.06.

[0304] 2-3. Measurement of volume resistivities R1 and R2 of domains exposed on the outer surface of the elastic layer and volume resistivity ρm of the matrix in the elastic layer

[0305] The measurement of the volume resistivities R1 and R2 of the domains exposed on the outer surface of the elastic layer and the volume resistivity of the matrix in the elastic layer can be performed as follows.

[0306] Specifically, considering the softness of the sample, current measurement in SIS-AFM mode was performed using a scanning probe microscope (SPM) (trade name: E-sweep, manufactured by Hitachi High-Tech Corporation). As the SPM cantilever, SI-DF3-R was used.

[0307] First, using a microtome (trade name: Leica EM FCS, manufactured by Leica Microsystems GmbH), an ultrathin sheet having a thickness of 1 μm was cut out from a cross section in the thickness direction of the conductive layer including the surface of the conductive member 1 at a cutting temperature of −100° C. Cutting of the ultrathin sheet was performed in the direction of the cross section perpendicular to the length direction of the conductive member (i.e., the thickness direction of the conductive layer) based on the direction in which the charge was transported for discharge.

[0308] Next, the ultrathin sheet was placed on a metal plate in an environment with a temperature of 23°C and a relative humidity of 50%. The vicinity of the surface of the sheet was observed with the above-mentioned SPM, and the domain exposed on the outer surface of the elastic layer was specified in the phase image. Thereafter, a current value image was acquired by applying 0.5V with respect to the portion other than the conductive particles in the first region and the portion other than the conductive particles in the second region in the cross section. Then, from the acquired current value image and the thickness of the sheet, the volume resistivity r1 of the first region and the volume resistivity r2 of the second region were calculated.

[0309] The above process was performed in the same manner for the following points. That is, the conductive layer of the conductive member 1 (length in the length direction: 224 mm) was divided into 5 equal parts in the length direction, further divided into 4 equal parts in the circumferential direction, and a total of 20 thin sheet samples were cut out one by one from each area. For each thin sheet sample, for each of the volume resistivities r1 and r2 at three positions of the domain exposed on the surface, measurements were performed at a total of 60 positions. The arithmetic mean values ​​of the volume resistivities r1 and r2 were defined as the volume resistivities R1 and R2, respectively.

[0310] Here, as described above, the first region is a region with a thickness of 0.1×Ld on the side farthest from the support body in the cross-section of the domain exposed on the outer surface, and the second region is a region with a thickness of 0.1×Ld on the side closest to the support body in the cross-section of the domain exposed on the outer surface, where Ld is the maximum length of the domain exposed on the outer surface in the thickness direction of the conductive layer.

[0311] The volume resistivity of the matrix in the conductive layer was measured as follows. That is, the volume resistivity was measured in the same manner as in the above method at three locations of the matrix portion in the thickness region from the outer surface to a depth of 0.1T to 0.9T of each fabricated sheet, i.e., at a total of 9 locations, where T is the thickness of the conductive layer. The arithmetic mean value was taken as the volume resistivity of the matrix.

[0312] The volume resistivity of the domains in the conductive layer is measured as follows: That is, in the measurement of the volume resistivity of the matrix described above, the volume resistivity of the domains is measured in the same manner as above, except that the measurement is performed at a position corresponding to the domain of the ultrathin sheet containing the conductive particle portion.

[0313] In the conductive member 1, R1 is 3.1×10 9 Ω·cm, R2 is 4.2×10 8 Ω·cm, satisfying the relationship of R1>R2, R1 / R2 is 7.4. The volume resistivity of the matrix is ​​9.1×10 13 The results are shown in Tables 10 and 11.

[0314] 2-4. Ratio of the cross-sectional area of ​​the conductive particles contained in the domain to the cross-sectional area of ​​the domain (S c Calculation of / S

[0315] Using the sheet on which platinum deposition was performed in the above 2.2, a cross-sectional image was obtained by photographing at a magnification of 20,000 times using a scanning electron microscope (SEM) (trade name: S-4800, manufactured by Hitachi High-Tech Corporation). Next, binarization was performed using image analysis software (product name: ImageProPlus, manufactured by Media Cybernetics, Inc.) so that the carbon black in the domains could be distinguished. In addition, an observation area having a size that accommodates one domain was extracted from the obtained binary image, and the cross-sectional area S of the domain and the cross-sectional area S of the carbon black as the conductive particles contained in the domain were calculated by using a counting function. c Then, through S c / S is the cross-sectional area ratio of the conductive particles in the calculation domain.

[0316] S of the conductive member 1 c / S was 28.0 area %. The results are shown in Table 10.

[0317] 2-5. Method for Confirming Interpenetrating Polymer Networks (IPN)

[0318] The interpenetrating polymer network (IPN) can be confirmed by, for example, the following method.

[0319] Using a microtome (trade name: Leica EM FCS, manufactured by Leica Microsystems GmbH), an ultrathin slice having a thickness of 100 nm was cut out from a cross section including the surface of the conductive member 1 at a cutting temperature of -100° C. Cutting of the ultrathin slice was performed in the direction of the cross section perpendicular to the length direction of the conductive member based on the direction in which charges were transported for discharge.

[0320] The prepared sheet is dyed with a colorant, a transmission electron microscope (trade name: H-7100FA, manufactured by Hitachi, Ltd.) is used to specify the domain, and then the first region and the second region of the cross section are photographed. Examples of dyes include osmium tetroxide, ruthenium tetroxide and phosphotungstic acid. Similarly, the matrix present at the same depth as the first region and the second region from the outer surface of the conductive layer is also photographed in the same manner. In the case of conductive member 1, the interpenetrating polymer network (IPN) can be confirmed by dyeing the rubber portion using osmium tetroxide as a dye. The rubber portion dyed by the reaction of the double bond between osmium tetroxide and the rubber is observed to be black, and the curable resin portion constituting the interpenetrating polymer network (IPN) is observed to be white. Therefore, it is determined that the rubber portion has an interpenetrating polymer network.

[0321] The monomers of the curable resin constituting the interpenetrating polymer network (IPN) were confirmed by taking out a piece of the impregnated area in the conductive layer, adding an organic base reagent such as tetramethylammonium hydroxide (TMAH), and using pyrolysis-gas chromatography-mass spectrometry (Pyr-GCMS). In the first area of ​​the conductive member 1, an interpenetrating polymer network (IPN) of a curable resin using acryl 1 as a monomer was confirmed. In addition, no interpenetrating polymer network was confirmed in the second area. The results are shown in Table 11.

[0322] 3. Evaluation as a charging member

[0323] Using the conductive member 1 as a charging roller, the fogging performance under a low charging bias condition was evaluated as follows.

[0324] A laser printer (trade name: HP LaserJet Pro M404, manufactured by HP Development Company, LP) was prepared as an electrophotographic image forming apparatus. Then, the conductive member 1 was installed as a charging roller of a process cartridge for the laser printer. In addition, the main body of the above-mentioned laser printer was modified so that an arbitrary voltage from an external power source (trade name: Model 615, manufactured by Trek Bicycle Corporation) was applied to the charging roller, the developing roller, and the intermediate transfer belt.

[0325] Next, in order to make the main body of the above-mentioned laser printer and the above-mentioned process box enter the measurement environment, the main body and the process box are left to stand for 48 hours in a high temperature and high humidity environment (HH environment) with a temperature of 30°C and a relative humidity of 80%. Next, the above-mentioned process box is loaded into the main body of the laser printer. Then, the external power supply is set so that the unexposed part (Vd) of the charging roller photosensitive member is 350V, the exposed part (Vl) of the photosensitive member is 100V, the development bias is 175V, and -(negative) 800V is applied to the charging roller as a charging bias. Then, a white solid image is output under the HH environment. The obtained white solid image is evaluated by the following method. Note that the evaluation result at this time is also referred to as the "number of initial fogging".

[0326] Evaluation method of fogging

[0327] Nine points of the white solid image were observed at 500 times magnification with an optical microscope, and the number of black dots caused by toner particles existing in a 1 mm square observation area was counted and defined as the number of fogs on paper.

[0328] When the conductive member 1 was used as a charging roller, the number of initial fogging was 187. The number of fogging after endurance was 123%. The results are shown in Table 11.

[0329] In this embodiment, the number of initial fogging is preferably set to 250 or less, particularly 200 or less, and the ratio of the number of fogging after durability to the number of initial fogging is suppressed to 130% or less, particularly 115% or less as indicators of the effects disclosed in the present application.

[0330] Next, under the same environment, while maintaining the image forming conditions, 10,000 images are formed by printing the letter "E" in the alphabet with a size of 4 points using the above-mentioned laser printer so that the coverage rate relative to the area of ​​A4 size paper is 1%. Thereafter, the conductive member 1 is taken out from the processing box and introduced into a new processing box as a charging roller. Thereafter, 1 white solid image is output under the same conditions as the "initial number of fogging". The fogging on the obtained white solid image is observed and evaluated by the following fogging evaluation method. The evaluation result at this time is also referred to as the "number of fogging after durability". The ratio of the number of fogging after durability to the number of initial fogging is defined as fogging after durability (%).

[0331] Here, the developer installed to the above-mentioned laser printer may be negatively charged. Therefore, when a white solid image is output, the developer is not initially transferred to the photosensitive member and the paper. However, as described above, under low charging bias conditions, an overcharged portion may be generated on the surface of the photosensitive member due to local strong discharge from the charging member. A small amount of positively charged developer present in the developer is transferred to the overcharged portion of the photosensitive member, with the result that even in the case where a white solid image is formed therein, black spots originating from the developer are observed, and so-called "reverse fogging" occurs in the white solid image. This phenomenon is very likely to occur under low charging bias conditions. Post-durability fogging also includes fogging caused by dirt attached to the surface of the conductive member 1 due to durable use of the conductive member 1.

[0332] Examples 2 to 23

[0333] Conductive members 2 to 23 were manufactured in the same manner as in Example 1 except that the blending was changed so that CMB was blended as shown in Table 6, MRC was blended as shown in Table 7, a conductive rubber composition was blended as shown in Table 8, a dip coating was blended as shown in Table 9, and a conductive layer was blended as shown in Table 10. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Tables 10 and 11.

[0334] Embodiment 24

[0335] The blending was changed so that CMB was blended as shown in Table 6, MRC was blended as shown in Table 7, a conductive rubber composition was blended as shown in Table 8, a dip coating was blended as shown in Table 9, and a conductive layer was blended as shown in Table 10, and the forming method of the conductive elastic roller 24 was changed as follows. Except for the above, the conductive member 24 was manufactured in the same manner as in Example 1. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Tables 10 and 11.

[0336] 1-6. Forming of Conductive Elastic Roller 24

[0337] A round bar having a total length of 244 mm and an outer diameter of 6 mm was prepared by subjecting the surface of free-cutting steel to chemical nickel plating. Next, an adhesive (trade name: Metaloc U-20, manufactured by TOYOKAGAKUKENKYUSHO CO., LTD.) was applied to the entire circumference of 222 mm excluding 11 mm at both ends of the round bar using a roll coater to prepare a support.

[0338] Next, a crosshead extruder (manufactured by MITSUBA MFG.CO., LTD.) was used to coat the conductive rubber composition 24 to make an unvulcanized rubber roller having a crown shape. A die with an inner diameter of 8.5 mm was mounted to the front end of the crosshead. The forming temperature of each of the barrel, screw and crosshead was set to 100°C. In order to form a crown shape, the support body was conveyed while changing the conveying speed, and the arithmetic mean speed when forming one charging roller was adjusted to 47 mm / second. At the die outlet, the conductive rubber flows out at the same speed as the core metal, so the average flow rate when forming one roller is 47 mm / second, which is the same as the conveying speed of the support body. The rotation speed of the screw was adjusted so that the outer diameter of the unvulcanized rubber roller at the center of the length was 8.6 mm relative to the conveying speed of the above-mentioned support body. The unvulcanized rubber roller after forming has a crown shape, an outer diameter of 8.5 mm at the center of the length, and an outer diameter of 8.44 mm at the position of +90 mm from the center of the length to both ends.

[0339] Thereafter, the unvulcanized rubber roller was vulcanized by heating at a temperature of 160° C. for 60 minutes in an electric furnace, both ends were cut off, and the length of the conductive rubber formed in the axial direction was set to 224 mm to produce the conductive elastic roller 24 .

[0340] Comparative Examples 1 to 4

[0341] Conductive members 25 to 28 were manufactured in the same manner as in Example 1 except that the blending was changed so that CMB was blended as shown in Table 6, MRC was blended as shown in Table 7, a conductive rubber composition was blended as shown in Table 8, a dip coating was blended as shown in Table 9, and a conductive layer was blended as shown in Table 10. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Tables 10 and 11.

[0342] [Table 6]

[0343]

[0344] [Table 7]

[0345]

[0346] [Table 8]

[0347]

[0348] [Table 9]

[0349]

[0350] [Table 10]

[0351]

[0352] In the table, S c / S represents the ratio (area %) of the cross-sectional area of ​​the conductive particles to the cross-sectional area of ​​the domain.

[0353]

[0354] In the table, the presence or absence of the MD structure indicates the presence or absence of the matrix-domain structure, Y indicates that R1>R2 is satisfied, and N indicates that R1>R2 is not satisfied.

[0355] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. An electrophotographic conductive member comprising: a support having an electrically conductive outer surface; and A conductive layer is provided on the outer surface of the support, wherein The conductive layer includes a matrix comprising a cross-linked product of a first rubber and a plurality of domains dispersed in the matrix, the plurality of domains comprising a cross-linked product of a second rubber and conductive particles, at least a portion of the plurality of domains is exposed on an outer surface of the electrophotographic conductive member, the outer surface of the electrophotographic conductive member is composed of the matrix and the exposed portion of the domain exposed on the outer surface of the electrophotographic conductive member, When an electrode is directly provided on the outer surface of the electrophotographic conductive member and an AC voltage with an amplitude of 1 V and a frequency of 1.0 Hz is applied between the outer surface of the support and the electrode under an environment with a temperature of 23° C. and a relative humidity of 50%, the impedance is 1.0×10 3 to 1.0×10 8 Ω, and When the domain exposed on the outer surface of the electrophotographic conductive member is a domain A, and in a cross section of the domain A in the thickness direction of the conductive layer, the maximum length of the domain A in the thickness direction of the conductive layer is Ld, The region with a thickness of 0.1×Ld on the side farthest from the support in the cross section of the domain A is the first region, and When the region with a thickness of 0.1×Ld on the side closest to the support in the cross section of the domain A is the second region, The volume resistivity R1 of the portion of the first region that is not the conductive particles and the volume resistivity R2 of the portion of the second region that is not the conductive particles satisfy R1>R2. 2 . The electrophotographic conductive member according to claim 1 , wherein the volume resistivity R1 and the volume resistivity R2 satisfy R1 / R2≧3.

0.

3. The electrophotographic conductive member according to claim 1 or 2, wherein the domains exposed on the outer surface of the electrophotographic conductive member further comprise at least one resin selected from the group consisting of (meth)acrylic resins, epoxy resins, vinyl ether resins and urea resins, and the resin forms an interpenetrating polymer network together with the first rubber and the second rubber.

4. The electrophotographic conductive member according to claim 1 or 2, wherein the first region further includes a (meth)acrylic resin which forms an interpenetrating polymer network together with the first rubber and the second rubber, and the second region does not include a (meth)acrylic resin.

5. The electrophotographic conductive member according to claim 1 or 2, wherein L is the length of the conductive layer in the length direction and T is the thickness of the conductive layer. When, for each of the cross-sections of the conductive layer in the thickness direction, an observation area of ​​15 μm square is placed at three positions in the thickness region from the outer surface of the conductive layer to a depth of 0.1T to 0.9T at a total of three positions including the center of the conductive layer in the length direction and two positions L / 4 from both ends of the conductive layer toward the center, among the domains observed in each of all 9 observation areas, the number ratio of domains with A / B values ​​of 1.00 to 1.10 is 80% or more, wherein A is the circumference of the domain, and B is the envelope circumference of the domain.

6. The electrophotographic conductive member according to claim 1 or 2, wherein in a domain observed in a cross section in the thickness direction of the conductive layer, a ratio S of a cross-sectional area of ​​the conductive particles to a cross-sectional area of ​​the domain is c / S is 20.0 to 35.0 area %.

7. The electrophotographic conductive member according to claim 1 or 2, wherein the volume resistivity ρm of the matrix is ​​1.0×10 8 to 1.0×10 17 Ω·cm.

8. The electrophotographic conductive member according to claim 1 or 2, wherein The first rubber includes at least one selected from the group consisting of isoprene rubber, butadiene rubber, styrene butadiene rubber, acrylonitrile-butadiene rubber and ethylene-propylene-diene rubber, and The second rubber includes at least one selected from the group consisting of isoprene rubber, butadiene rubber, styrene butadiene rubber, acrylonitrile-butadiene rubber, and ethylene-propylene-diene rubber.

9. The electrophotographic conductive member according to claim 1 or 2, wherein the absolute value of the difference in solubility parameter between the first rubber and the second rubber is 0.4 to 5.0 (J / cm 3 ) 0.5 .

10. The electrophotographic conductive member according to claim 9, wherein The combination of the first rubber and the second rubber is Styrene butadiene rubber and acrylonitrile butadiene rubber, Acrylonitrile butadiene rubber and styrene butadiene rubber, Acrylonitrile-butadiene rubber and butadiene rubber, Ethylene-propylene-diene rubber and acrylonitrile-butadiene rubber, Ethylene-propylene-diene rubber and styrene-butadiene rubber, Isoprene rubber and styrene butadiene rubber, Butadiene rubber and acrylonitrile-butadiene rubber, Styrene-butadiene rubber and ethylene-propylene-diene rubber, or Styrene butadiene rubber and isoprene rubber.

11. A process cartridge configured to be detachably mounted to a main body of an electrophotographic image forming apparatus, the process cartridge comprising the electrophotographic conductive member according to any one of claims 1 to 10. 12 . An electrophotographic image forming apparatus comprising the electrophotographic conductive member according to claim 1 .

13. The electrophotographic image forming apparatus according to claim 12, wherein The electrophotographic image forming apparatus includes an electrophotographic photosensitive member and a charging member for charging the electrophotographic photosensitive member, and The charging member is the electrophotographic conductive member.

14. The electrophotographic image forming apparatus according to claim 13, wherein a charging bias applied between the electrophotographic photosensitive member and the charging member is -700 to -900 V.

Citation Information

Patent Citations

  • Conductive member, process cartridge and electro-photographic image formation apparatus

    JP2020166209A